Application of the reconstruction and substance balance method to the study of the degradation of soil fertility in the Semiarid Pampas Region (Semiárida, 2020)
The bas is of the method of reconstruction and balance sheet of substances are given. The required parameters for this application to soil degradation studies in the semiarid region are considered. A CaC03- balancesheet of an Ustipsamment is given as an example.
Keywords: soil